PENGARUH STRATEGIC HUMAN RESOURCE MANAGEMENT, TRANSFORMATIONAL LEADERSHIP DAN INFORMATION SHARING TERHADAP ORGANIZATIONAL PERFORMANCE(Studi Kasus Pada Rumah Sakit Umum Daerah Kota Depok) - Veronica Titik Yuliarti, (2022)
This study analyzes Strategic Human Resource Management, Transformational Leadership and Information Sharing on Organizational Performance (Case Study at the Depok City Regional General Hospital). The purpose of the study was to prove and analyze the influence of Strategic Human Resource Management, Transformational Leadership and Information Sharing on Organizational Performance (Case Study at the Depok City Regional General Hospital). This research is quantitative by distributing questionnaires to 53 employees in the Depok City Hospital. This study uses the Partial Least Square (PLS) method with the Smart-PLS 3.0 program. The results of data analysis show that (1) Strategic Human Resource Management has a significant effect on Organizational Performance (2) Transformational Leadership has a significant effect on Organizational Performance (3) Information Sharing has a significant effect on Organizational Performance (4) Strategic Human Resource Management has a significant effect on Organizational Performance through Information Sharing (5) Transformational Leadership has an effect on Organizational Performance through Information Sharing (6) Strategic Human Resource Management, Transformational Leadership and Information Sharing together have a significant effect on Organizational Performance of Employees in the Depok City Regional General Hospital in accordance with Decree No. 445 /01/SK/RSUD/2022 concerning the Determination of the Head of Installation, Head of Room and Head of Unit at the Depok City Regional General Hospital.